Engagement at work: An analysis of professionals industries (Research, Society and Development, 2019)
The complexity and the depth of the human needs denotes a great amplitude of variety of aspects, factors and situations that the organizations had started to watch and analyze more often. The objective of this study is to analyze the work engagement of the professionals who works in industries, the Midwest region on Paraná. This research is an applied nature, with descriptive objective and qualitative approach. As instrument of study, the Utrecht Work Engagement Scale (UWES) composed of 17 items, beyond of socioeconomic quiz. The results characterizes the sample as, the main respondents, male, age range younger, high school, single and that studies and works. About the UWES, the data point out to the biggest average to the dimension dedication. However, when watched the coefficient of variation, the dimension vigor has the smaller dispersal, that is the small dispersal, demonstrating that the searched professionals has more energy, vitality, mental resilience and persistence at work. The smaller average is the dimension absorption, highlighted high dispersal as the condition of turn off from the work and perception of time and the around. In conclusion, the level of work engagement of professionals in industry is medium.